Pemanfaatan AI dalam Pembelajaran PAK: Kompetensi Guru, Karakter, dan Etika Kristen - Nadeak, Sanjay Mendra Jubil Kampus; Wenda, Pisman; Sunyap, Yefta; Inggabow, Lindert; Arfusau, Albert (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2026)
The development of artificial intelligence (AI) has brought significant changes to the world of education, including the implementation of Christian Religious Education (PAK) at various levels of education. The presence of AI provides opportunities for teachers to enhance the effectiveness of learning by providing learning resources that are more diverse, interactive, and easily accessible. However, the utilization of this technology also requires teachers to possess adequate competencies to ensure that the use of AI continues to support educational goals oriented toward character formation and Christian values. Emerging trends indicate that the use of AI in learning is becoming increasingly widespread, but not all teachers possess the necessary pedagogical readiness, digital literacy, and understanding of Christian ethics to integrate this technology into the learning process. This study aims to analyze the use of AI in PAK education from the perspectives of teacher competence, character development, and Christian ethics. This study employs a library research method with a descriptive-analytical approach through the analysis of various relevant literature. The results indicate that AI can serve as an effective tool to support innovation in PAK education and enhance teachers’ professional competence. Furthermore, the targeted use of AI can strengthen students’ character development through contextual and reflective learning. This study concludes that the integration of AI into Christian Religious Education must be grounded in a strong foundation of Christian ethics to ensure that technology is used responsibly, wisely, and remains centered on Christian values.